Evaluating the Prognostic Role of Monocytopenia in Chemotherapy-Induced Febrile Neutropenia Patients Treated with Granulocyte Colony-Stimulating Factor - Alshari O; Al Zu'bi YO; Al Sharie AH; Wafai FH; Aleshawi AJ; Atawneh FH; Obeidat HA; Daoud MN; Khrais MZ; Albals D; Tubaishat F (Dove Medical Press, 2021)
Osama Alshari,1 Yazan O Al Zu'bi,2 Ahmed H Al Sharie,2 Farouk H Wafai,2 Abdelwahab J Aleshawi,2 Farah H Atawneh,3 Hasan A Obeidat,2 Majd N Daoud,2 Mohammad Z Khrais,4 Dima Albals,5 Faize Tubaishat6 1Division of Oncology, Department of Internal Medicine, Faculty of Medicine, Jordan University of Science & Technology, Irbid, Jordan; 2Faculty of Medicine, Jordan University of Science & Technology, Irbid, Jordan; 3Department of Medical Laboratory Sciences, Faculty of Applied Medical Sciences, Jordan University of Science and Technology, Irbid, Jordan; 4Department of Internal Medicine, King Hussein Cancer Foundation and Center, Amman, Jordan; 5Department of Medicinal Chemistry and Pharmacognosy, Faculty of Pharmacy, Yarmouk University, Irbid, Jordan; 6Division of Oncology, Department of Internal Medicine, Al Bashir Hospital, Amman, JordanCorrespondence: Osama AlshariDivision of Oncology, Department of Internal Medicine, Faculty of Medicine, University of Science & Technology, P. O. Box: 3030, Irbid, 22110, JordanEmail osamasalshari@gmail.comObjective: Chemotherapy-induced febrile neutropenia is a common and serious oncological emergency which carries a substantial mortality and morbidity. The main objective of this study is to evaluate the usage of absolute monocyte count (AMC) at presentation as a prognostic factor for patients with chemotherapy-induced febrile neutropenia who were subsequently treated with granulocyte colony-stimulating factor (G-CSF).Study Design: The electronic medical records of our center were used retrospectively to identify patients diagnosed with unprecedented chemotherapy-induced febrile neutropenia treated with G-CSF between January 2010 to December 2020 and diagnosed with solid and hematological malignancies. Patient's demographics, disease characteristics and laboratory investigations were extracted. Disease progression measures were statistically compared between the study groups in the short-term period of follow-up (six days) including absolute neutrophil count (ANC), ANC difference compared to the baseline readings, hospitalization period, and mortality.Results: A total of 80 patients were identified and categorized into two groups namely monocytopenia (n = 34) and non-monocytopenia (n = 46) with an AMC cutoff point of 0.1× 109 cells/L. The monocytopenia group exhibited a worse prognosis with lower ANC values and slower improvement illustrated by the low ANC difference values at all follow up points (P-value ≤ 0.05) apart from day 5. A statistically significant lower hospitalization period was also observed in the non-monocytopenia group (P-value = 0.006). Linear regression analysis evaluated the association between AMC values at admission and ANC values at admission along with subsequent days of follow up which were found to be statistically significant (P-value ≤ 0.05). Receiver operating characteristic curves suggest a satisfactory predictability of ANC changes by AMC values at admission, days1, 2, 3, 4 and 6.Conclusion: Monocytopenia holds a worse prognosis in chemotherapy-induced febrile neutropenia patients treated with G-CSF. In addition, AMC values at presentation represents a potential risk factor that can predict short-term changes regarding ANC measures.Keywords: febrile neutropenia, granulocyte colony-stimulating factor, G-CSF, chemotherapy, absolute monocyte count, monocytopenia, absolute neutrophil count